2018
DOI: 10.1097/phh.0000000000000623
|View full text |Cite
|
Sign up to set email alerts
|

Local Boards of Health Characteristics Influencing Support for Health Department Accreditation

Abstract: Background Local boards of health (LBoHs) serve as the governance body for 71% of local health departments (LHDs). Purpose To assess the impact of LBoH governance functions and other characteristics on the level of LBoH support of LHD accreditation. Methods Data from 394 LHDs that participated in the 2015 Local Boards of Health Survey were used for computing summative scores for LBoHs for domains of taxonomy and performing logistic regression analyses in 2016. Results Increased odds of an LBoH directing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…35,36 For example, one study found that LHDs with larger boards and greater community input were more likely to be accredited. 37 Other studies, however, found that most members of local boards of health were White (96%) and male (60%) 18 and tended to be appointed rather than elected, 38 suggesting these board members may not be entirely representative of the communities they serve. To the extent these differences result in incomplete or inaccurate awareness of local health needs, it may explain why the presence of a local board of health was not correlated with greater access to health services.…”
Section: Discussionmentioning
confidence: 98%
“…35,36 For example, one study found that LHDs with larger boards and greater community input were more likely to be accredited. 37 Other studies, however, found that most members of local boards of health were White (96%) and male (60%) 18 and tended to be appointed rather than elected, 38 suggesting these board members may not be entirely representative of the communities they serve. To the extent these differences result in incomplete or inaccurate awareness of local health needs, it may explain why the presence of a local board of health was not correlated with greater access to health services.…”
Section: Discussionmentioning
confidence: 98%
“…These characteristics have been shown to be associated with whether LHDs were involved in accreditation or not. 20,[25][26][27]36 For example, LBoH authority, LHDs' governance structure, and LHDs' jurisdiction population have been associated with LHDs' decisions to participate in accreditation. 20,25,26 Therefore, these characteristics may be similarly important for understanding factors that could affect performance scores of LHDs that have completed accreditation assessments in each of the standards.…”
Section: Discussionmentioning
confidence: 99%
“…20,[25][26][27]36 For example, LBoH authority, LHDs' governance structure, and LHDs' jurisdiction population have been associated with LHDs' decisions to participate in accreditation. 20,25,26 Therefore, these characteristics may be similarly important for understanding factors that could affect performance scores of LHDs that have completed accreditation assessments in each of the standards. However, many of these characteristics examined did not show significant variation between the clusters except in their jurisdictionsʼ population size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations